Lactobacillus helveticus and Lactobacillus plantarum modulate renal antioxidant status in a rat model of fructose-induced metabolic syndrome - Korkmaz, Omer Adil; Sadi, Gokhan; Kocabas, Aytac; Yildirim, Onur Gokhan; Sumlu, Esra; Koca, Halit Bugra; Nalbantoglu, Barbaros; Pektas, Mehmet Bilgehan; Akar, Fatma (INST BIOLOSKA ISTRAZIVANJA SINISA STANKOVIC, 2019)
High dietary fructose intake causes a metabolic disorder and augments the risk of chronic kidney disease most likely due to oxidative stress. Probiotics could have antioxidant, antiinflammatory and immunoregulatory properties. The present study examined the influence of Lactobacillus helveticus and Lactobacillus plantarum supplementation on dietary fructose-induced metabolic changes and renal antioxidant/oxidant status of rats. Male Wistar rats were divided into four groups as follows: control; fructose; fructose plus L. helveticus; fructose plus L. plantarum. Fructose was given to the rats as a 20% solution in drinking water for 15 weeks. The probiotic supplementation was applied by gastric gavage once a day for six weeks. Several metabolic parameters in the plasma, gene and protein expressions of the main antioxidant enzymes in renal tissues of rats were measured. Dietary fructose-induced elevations in plasma insulin, triglyceride, VLDL, creatinine as well as renal urea levels were alleviated after treatment with L. helveticus and L. plantarum. Moreover, L. helveticus and L. plantarum supplementation recovered the changes in renal protein expression level of SOD1, SOD2 and CAT. In conclusion, supplementation with L. helveticus and L. plantarum has an improving effect on specific metabolic parameters and renal antioxidative enzymes in a fructose-induced metabolic disorder.
Keywords: dietary fructose; renal antioxidant status; antioxidant enzymes; Lactobacillus helveticus; Lactobacillus plantarum; OXIDATIVE STRESS; INSULIN-RESISTANCE; PROBIOTIC STRAINS; LIPID-METABOLISM; CURVATUS HY7601; L-CARNITINE; URIC-ACID; INFLAMMATION; DYSFUNCTION; KIDNEY; Life Sciences & Biomedicine - Other Topics